2021
DOI: 10.1002/pc.26410
|View full text |Cite
|
Sign up to set email alerts
|

The effect of halloysite nanotube modification on wear behavior of carbon‐aramid fiber reinforced hybrid nanocomposites

Abstract: In this study, the carbon-aramid fiber reinforced hybrid composites are fabricated using a vacuum-assisted hand lay-up method using halloysite nanotubes (HNTs) modified epoxy matrix. Ball-on-disk wear tests are performed to analyze the tribological effect of neat and HNTs-added specimens at 10, 15, and 20 N loads and 1 m/s sliding speed. Additionally, the wear rate and friction coefficient results are obtained to investigate the effect of the HNTs on the tribological behavior of hybrid composites. The wear mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…The modified‐adhesive joints' increased toughness is generally attributed to the HNTs governed nanoscale toughening mechanisms. [ 22–27,38,39 ]…”
Section: Resultsmentioning
confidence: 99%
“…The modified‐adhesive joints' increased toughness is generally attributed to the HNTs governed nanoscale toughening mechanisms. [ 22–27,38,39 ]…”
Section: Resultsmentioning
confidence: 99%
“…For example, nanosilica, nanocarbon tubes, and various nanosized fillers or intensifiers are added to the materials to form composite materials. 36,37 The improvements caused by nanomaterials can be attributed to two aspects: (1) Nanosized particles of nanomaterials can cause changes in physical aspects, resulting in filling effects, and further improvement in mechanical properties [38][39][40] ; (2) Nanomaterials have higher surface energies, which strengthens the cementation between adjacent materials. [41][42][43][44] Among various nanomaterials, nano-SiO 2 (NS) is a useful nanomaterial, and it has low production costs and a good cementation effect.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Introducing nanofillers into the matrix, according to earlier studies, can inhibit damage propagation through various nano-and micro-scale toughening mechanisms. [25][26][27][28][29] Graphene nanoplatelets (GNPs), carbon nanotubes (CNTs), nylon 6.6 nanofibers and nanosilicates are among the nanofillers being investigated to increase damage tolerance in FRP laminates after impact testing by triggering additional toughening mechanisms, including crack bridging and particle debonding. [30][31][32][33] Safamanesh et al found that incorporating the graphene oxide diminished the damaged area and improved damage tolerance, as well as the peak force and absorbed energy of the composite, were increased by 44% and 95%, respectively.…”
Section: Introductionmentioning
confidence: 99%